2010
DOI: 10.1002/nau.20892
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder: Is there a link to the metabolic syndrome in men?

Abstract: It is becoming increasingly clear that a variety of metabolic, cardiovascular, and endocrine factors contribute to male pelvic health. In particular, a growing body of evidence suggests a relationship between lower urinary tract symptoms, benign prostatic hyperplasia, overactive bladder, erectile dysfunction, and the metabolic syndrome. This article explores these relationships, focusing on the role of the autonomic nervous system and hyperinsulinemia, together with their implications for urological practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 40 publications
2
57
0
3
Order By: Relevance
“…In line with these clinical findings, bladder dysfunction has also been reported in rat models of metabolic syndrome (Chung et al 2013;Lee et al 2008). In line with others (Bunn et al 2015;Kirby et al 2010), we conclude that metabolic syndrome apparently exhibits a more robust association with LUTS than its individual components of dyslipidemia and diabetes.…”
Section: Clinical Associations Between Atherosclerosis Risk Factors Asupporting
confidence: 92%
“…In line with these clinical findings, bladder dysfunction has also been reported in rat models of metabolic syndrome (Chung et al 2013;Lee et al 2008). In line with others (Bunn et al 2015;Kirby et al 2010), we conclude that metabolic syndrome apparently exhibits a more robust association with LUTS than its individual components of dyslipidemia and diabetes.…”
Section: Clinical Associations Between Atherosclerosis Risk Factors Asupporting
confidence: 92%
“…And, MetS are known to cause autonomic sympathetic overactivity through complex mechanisms 2,3 . It is suggested that overactivity of the sympathetic nervous system takes part in the development of BPH and LUTS 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the parasympathetic nervous system can cause detrusor muscle contraction and may therefore contribute to detrusor over-activity, which is characteristic of the prevalence of storage symptoms [51].…”
Section: Discussionmentioning
confidence: 99%